Fixed-dose combination of perindopril and indapamide: perspectives in hypertensive patients with inadequately controlled blood pressure - I. E. Chazova; T. V. Martynyuk (Кардиоваскулярная терапия и профилактика)
Combined ACE inhibitor / diuretic therapy is one of the rational antihypertensive combinations for treating arterial hypertension (AH) patients. In a pharmaco-epidemiological, multicenter, open prospective study STRATEGY (Comparative program aSsessing noliprel effecTiveness in hypeRtensive pATiEnts with inadequatelY controlled blood pressure), it is planned to study clinical effectiveness and tolerability of perindopril / indapamide combination in more than 2000 patients with mild to moderate AH, in realworld clinical settings, during 4 months. The aim of the study is to compare rates of blood pressure (BP) reduction during combined perindopril / indapamide (Noliprel® or Noliprel® forte) therapy in the following clinical situations: initial antihypertensive therapy in newly diagnosed AH patients; continuous AH therapy in patients with BP above target levels, or with adverse effects of other agents; adding the combination to baseline therapy, in order to enhance antihypertensive effect.